Regional Economic Integration of Bosnia and Herzegovina – Obstacles for (Re)integration - Zinka Grbo (LeXonomica, 2021)
Discussions: Regional Economic Integration of Bosnia and Herzegovina – Obstacles for (Re)integrationRazprave: Regionalna ekonomska integracija Bosne in Hercegovine - ovire in (re)integracija